Anisotropy and tension–compression asymmetry modeling of the room temperature plastic response of Ti–6Al–4V. (April 2015) - Tuninetti, V.; Gilles, G.; Milis, O.; Pardoen, T.; Habraken, A.M.
Highlights: The Ti–6Al–4V is characterized in the three orthogonal directions of the material. A new methodology for plastic anisotropy characterization based on inverse modeling of the axial strain field of compression specimens is proposed. The methodology is applied for the identification of the macroscopic orthotropic yield criterion "CPB06" adapted for hcp metals. A constraint of parameters should be imposed when identifying CPB06 with missing shear tests in one material direction. The methodology is validated with accurate FEM simulations of tests on specimens involving multiaxial strain fields. Abstract: The mechanical behavior of the alloy Ti–6Al–4V is characterized using uniaxial tension, uniaxial compression, simple shear and plane strain tests in three orthogonal material directions. The experimental results reveal tension/compression asymmetry, anisotropic yielding and anisotropic strain-hardening. These features are incorporated into an elasto-plastic constitutive law based on the macroscopic orthotropic yield criterion "CPB06" adapted to hexagonal metals. A new identification method for the yield criterion parameters is proposed by inverse modeling of the axial strain field of compression specimens in the three orthogonal directions of the material. The sensitivity of different sets of material parameters to the identification method is also analyzed and the capacity of the model to accurately predict the forces and displacement field is discussed. A validation of the best set of identified CPB06 material parameters is performed by comparing the load–displacement curves in different loading directions for tensile tests on notched round bars with different levels of stress triaxiality and for compression tests on elliptical cross-section specimens, both tests involving multiaxial strain fields and large deformations.